EVALUASI KINERJA BMT AL FATAYA DALAM MENINGKATKAN DAYA SAING BERDASARKAN PRINSIP EKONOMI SYARIAH - Fadhil, Muhamad; Pertiwi, Ruspita Rani; Wira, Ahmad; Kurnia, Rahmat (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2025)
This research is based on the background of BMT Al Fataya having agreat opportunity to become a pilot BMT at both the Payakumbuh City andProvincial levels. This is because BMT Al Fataya is growing rapidly from year toyear in terms of the number of members and branch offices. Therefore, theformulation of the problem in this research is how to evaluate the performance ofBMT Al Fataya in increasing competitiveness and what is the view of shariaeconomics towards evaluating the performance of BMT Al Fataya in increasingcompetitiveness. Data collection techniques are observation, interviews anddocumentation with qualitative descriptive analysis using purposive samplingtechniques. Based on the results of this research, the performance evaluationcarried out by BMT Al Fataya is good, where the strategy has been achieved andimplemented well and evaluated regularly. Apart from that, in implementing thestrategy concept of sharia economics has also been implemented.